Um processo para produção de game concept com base em planejamento estratégico - Ferreira, Tiago Keller (2010)
In a general context, electronic games have been evolving into more complex software, as well as development cost and resources invested in them have been also increased despite the considerable technological advances and new software tools being produced and deployed. The Brazilian context regarding game development gives a picture of how it currently operates with restricted resources and still shows the clear need for improved financial support. In order to fill this gap and overcome the lack of sufficient funds, the Brazilian companies usually turn their attention to creactivity, management and strategy to reach the status of a real competitive company. This article aims to present the use of strategic planning in the process of creating game concepts so it can be applied to maximize the chance of success of a low-budget game, approching the development to a more strategic process. This work presents a case study in which strategic planning is applied to the process of creating the game concept in a game developer company.